Determinants of Occupational Health and Safety Disclosure: An Empirical Study of Property, Real Estate, and Building Construction Companies on IDX - Sindy Astuti; Aminah (Ilomata International Journal of Tax and Accounting, 2023)
Occupational Health and Safety Disclosure (OHSD) is essential to provide the public and stakeholders with more information about a company. In particular, OHSD still needs further research because the work accidents in Indonesia are currently excessive, but not all companies disclose it. OHSD is also crucial for corporate sustainability. The primary objective of this study is to conduct an empirical study of the impact of Profitability, Leverage, and The Size of the Board of Commissioners on OHSD. The research method used in this study is quantitative and secondary data obtained from the annual reports and sustainability reports of the property, real estate, and building construction companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The sampling technique used is purposive sampling, with 81 samples. Data analysis used panel data regression with a Random Effect Model (REM). The study concluded that Profitability and Leverage (DER) significantly and positively affect OHSD. However, the size of the Board of Commissioners has a negative and significant effect on OHSD. The research results imply the Occupational Health and Safety Disclosure as material for preparing company policies. For academics, this research is expected to expand the financial accounting literature on OHSD from the stakeholder theory perspective.